External training load and rating of perceived exertion comparison between different playing styles and winning vs. losing matches in elite tennis - Tóth, Péter János; Csáki, István; Négyesi, János; Dobos, Károly; Havanecz, Krisztián; Sáfár, Sándor; Ökrös, Csaba (Frontiers in Sports and Active Living, 2025)
IntroductionThis study aims to compare different playing styles on external training load and rating of perceived exertion (RPE) in elite Hungarian junior tennis players during the off-season in winning vs. losing matches.MethodsSixteen elite male junior tennis players from the same club participated in this study (aggressive baseliner: n = 9; counterpuncher: n = 7), and each player was required to play three simulated matches. We measured eleven activity profiles, fourteen external training load variables, and the subjective RPE parameter for all matches. For the activity profile measure, we used video cameras, and for the external training load, we used a 10 Hz global navigation satellite system (GNSS) with integrated 100 Hz inertial measurement units (IMU).ResultsFor the different playing styles, we found that aggressive baseliner players produce more high-intensity (≤−2 m/s2) decelerations (p = 0.015; r = 0.35), and higher other stroke load values (p = 0.009; r = 0.38), than counterpuncher players. However, in the other external training load and RPE variables we did not find any significance differences (p > 0.05). For the match outcomes, we found that the running load (p = 0.013; r = 0.50) values were higher in winning situations, while the RPE (p = 0.000; r = 0.79) values were greater in losing matches. However, apart from this, we did not find any significant differences in the other parameters (p > 0.05).DiscussionIn conclusion, aggressive baseliner players must develop more movements toward the net and the necessary adjustment steps for volleys. Furthermore, running activities do not necessarily influence match outcomes, therefore, it is important to place more emphasis on the development and monitoring of technical and tactical situations. Based on these points, we recommend that coaches integrate the development of specific footwork and dominant technical-tactical actions simultaneously on the court, so that players can better incorporate these elements into their game.